Word Formation Analysis of English Slang Words in The Kalogeras Sisters YouTube Videos (English Language and Literature (JELL), 2026)
This study aims to analyse the types of word formation and the functions of slang words found in The Kalogeras Sisters YouTube videos. This study employed a descriptive method. The analysis of word formation types was based on Yule’s (2017) theory, supported by Plag (2018) and Lieber (2016), while the functions of slang were analysed using the theories proposed by Byrne (2017), Bergen (2016), and Allan (2018). The data were collected from conversations in several videos uploaded on The Kalogeras Sisters YouTube channel from December 2024 to January 2025, which consist of slang words used by Sunday, Demitra and Eli in their daily conversations. The analysis began by identifying and classifying the types of word formation and the functions of slang words found in the data. The results show that the most dominant type of word formation is clipping, followed by derivation,acronym, blending, conversion, compounding, borrowing, and multiple processes. At the same time, coinage and backformation are not found.Meanwhile, in terms of function, the most dominant function of slang is to convey certain thoughts, followed by to mock, to create more close-knit interaction, to express closeness in social relationships, to express anger, and to create a comfy energy.
Keywords: Morphology, Word Formation, Slang, YouTube, Kalogeras Sisters.